THE ROLES OF COMMUNITY SERVICE DEPARTMENT (DPM) UNIVERSITY OF DARUSSALAM GONTOR IN FOSTERING THE MORALS OF STUDENTS AT TPA AL-AMIN, BRAHU, SIMAN, PONOROGO PERIOD 2019-2020 - Gunandar, Alvhi Sahkrin (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2023)
It can be ensured that all campuses implement one of the elements of the Tri Darma of College, therefore Darussalam Gontor University has created a special institution aimed at community service. DPM UNIDA Gontor is one of the student activity units that is expected to be able to have a positive impact on the surrounding community. Because seeing the increasing moral crisis of the students, DPM UNIDA Gontor tried to present a solution to this. Due to the large number of community requests to the UNIDA campus in overcoming the existing problems, the UNIDA Gontor DPM began operating in the Fostered Landfill teaching activities in the area around Siman Ponorogo sub-district. This study aims to determine: 1) The role of DPM UNIDA Gontor in fostering student morals, 2) Inhibiting and supporting factors in fostering student morals. This research is a qualitative descriptive study. In collecting data, the researchers used three methods, namely: 1) Observation, 2) Interview and 3) Documentation. Meanwhile, in analyzing data, researchers used three types of data analysis as suggested by J. Moloeng, namely data reduction, data presentation, and conclusion drawing. Based on the results of the study, the following conclusions can be drawn: 1) Activities organized by DPM UNIDA Gontor are very instrumental in fostering the morals of students, 2) The training activities held by DPM UNIDA Gontor specifically for teachers, become one of the supporting factors to facilitate teachers in fostering the morals of students. Based on the results of the study, the gave suggestions: 1) To DPM UNIDA Gontor to maintain and enhance further research activities that are already good and positive. 2) To all local residents to cooperate with each other to support the implementation of moral guidance activities for students. 3) TPA directors should arrange special time for mentoring activities for local instructors, in order to increase their knowledge in teaching. 4) To TPA teachers from UNIDA Gontor to give awards to students who have good character, so that they are all motivated to continue doing good. 5) For further researchers to examine the good traditions of UNIDA GONTOR, namely Motto and Five Spirits. This needs to be examined because it has an influence on the success of UNIDA GONTOR in producing the best graduates.